Take the 2-minute tour ×
Mathematica Stack Exchange is a question and answer site for users of Mathematica. It's 100% free, no registration required.

Trying to figure out if the infinite triple series has a nice closed form. It seems Mathematica
is unable to help us here. Numerically, things remain the same, no response. Could you help?

N[ Sum[ n! k! m!/(n + k + m + 2)!, {n, 0, ∞}, {k, 0, ∞}, {m, 0, ∞}]]

EDIT: in 2 variables, the double series evaluates to $\pi^2/6$.

share|improve this question
    
You can do two of the sums, one at a time. –  b.gatessucks Dec 23 '13 at 9:10
    
The answer is $\pi^2/4$ and it can be guessed via Mathematica. Shortly, evaluating the sums one by one. Now I'm going to sleep, will write tomorrow if somebody wouldn't do it earlier. –  Andrew Dec 23 '13 at 20:49
    
@Chris'ssis please see the answer below. Numerical checking give near enough values. –  Andrew Dec 24 '13 at 8:27

2 Answers 2

up vote 5 down vote accepted

Doing sums one by one explicitly specifying parameters helps:

f1 = Sum[ n! k! m!/(n + k + m + 2)!, {k, 0, ∞}, 
          Assumptions -> k ∈ Integers && m ∈ Integers && k > 0 && m > 0]

gives $$\frac{\Gamma (m+1) \Gamma (n+1)}{(m+n+1)^2 \Gamma (m+n+1)}$$

f2 = Sum[ f1, {m, 0, ∞}, Assumptions -> n ∈ Integers && n > 0]

$$\frac{\, _3F_2(1,1,n+1;n+2,n+2;1)}{(n+1)^2}$$ Mathematica doesn't evaluate the last Sum[ f2, {n, 0, ∞}], but here a very handy FindSequenceFunction can be used:

tt = Table[f2, {n, 1, 10}] // Expand

$$\left\{2-\frac{\pi ^2}{6},\frac{\pi ^2}{6}-\frac{3}{2},\frac{31}{18}-\frac{\pi ^2}{6},\frac{\pi ^2}{6}-\frac{115}{72},\frac{3019}{1800}-\frac{\pi ^2}{6},\frac{\pi ^2}{6}-\frac{973}{600},\frac{48877}{29400}-\frac{\pi ^2}{6},\frac{\pi ^2}{6}-\frac{191833}{117600},\frac{5257891}{3175200}-\frac{\pi ^2}{6},\frac{\pi ^2}{6}-\frac{5194387}{3175200}\right\}$$

f3 = FullSimplify[ FindSequenceFunction[tt, n], n ∈ Integers && n > 0]

$$ \frac{1}{2} \left(\psi ^{(1)}\left(\frac{n+1}{2}\right)-\psi ^{(1)}\left(\frac{n+2}{2}\right)\right) $$ Somehow on less than ten terms in $tt$ FindSequenceFunction doesn't work here.

So

Sum[ f3, {n, 0, ∞}]

is a telescopic sum and is equal to the first term $\frac12\psi ^{(1)}\left(\frac{1}{2}\right)=\frac{\pi ^2}{4}$.

share|improve this answer
1  
This seems too nice to be true ... –  Chris's sis Dec 24 '13 at 12:54
    
FindSequenceFunction is just a guess, since it operates on a finite portion of the sequence; is that not correct? –  robjohn Dec 27 '13 at 8:50
    
@robjohn yes. $~$ –  Andrew Dec 27 '13 at 9:01
    
Nonetheless, nice answer! (+1) –  robjohn Dec 27 '13 at 9:04

Note that $$ \begin{align} &\frac{k!}{(n+k+1)!}-\frac{(k+1)!}{(n+k+2)!}\\ &=(n+k+2)\frac{k!}{(n+k+2)!}-(k+1)\frac{k!}{(n+k+2)!}\\ &=(n+1)\frac{k!}{(n+k+2)!}\tag{1} \end{align} $$ Sum $(1)$ for $k\ge0$ and divide by $n+1$ to get $$ \sum_{k=0}^\infty\frac{k!}{(n+k+2)!}=\frac1{(n+1)(n+1)!}\tag{2} $$ Applying $(2)$ to the triple sum yields $$ \begin{align} \sum_{n=0}^\infty\sum_{m=0}^\infty\sum_{k=0}^\infty\frac{n!m!k!}{(n+m+k+2)!} &=\sum_{n=0}^\infty\sum_{m=0}^\infty\frac{n!m!}{(n+m+1)(n+m+1)!}\tag{4} \end{align} $$ Now, consider $$ \begin{align} a_n &=\sum_{m=0}^nm!(n-m)!\\ &=n!+\sum_{m=0}^{n-1}m!(n-m-1)!\,((n+1)-(m+1))\\ &=n!+(n+1)\sum_{m=0}^{n-1}m!(n-m-1)!-\sum_{m=0}^{n-1}(m+1)!(n-m-1)!\\ &=n!+(n+1)a_{n-1}-(a_n-n!)\tag{5}\\ a_n&=n!+\frac{n+1}{2}a_{n-1}\tag{6}\\ b_n&=\frac{2^n}{n+1}+b_{n-1}\quad\text{where }b_n=\frac{2^n}{(n+1)!}a_n\tag{7} \end{align} $$ Thus $$ a_n=\frac{(n+1)!}{2^n}\sum_{k=0}^n\frac{2^k}{k+1}\tag{8} $$ Using $(8)$, the sum in $(4)$ is $$ \begin{align} \hspace{-1cm}\sum_{m=0}^\infty\sum_{n=0}^\infty\frac{n!m!}{(n+m+1)(n+m+1)!} &=\sum_{m=0}^\infty\sum_{n=m}^\infty\frac{(n-m)!m!}{(n+1)(n+1)!}\tag{9}\\ &=\sum_{n=0}^\infty\sum_{m=0}^n\frac{(n-m)!m!}{(n+1)(n+1)!}\tag{10}\\ &=\sum_{n=0}^\infty\frac{a_n}{(n+1)(n+1)!}\tag{11}\\ &=\sum_{n=0}^\infty\sum_{k=0}^n\frac{2^{k-n}}{(n+1)(k+1)}\tag{12}\\ &=\sum_{k=0}^\infty\sum_{n=k}^\infty\frac{2^{k-n}}{(n+1)(k+1)}\tag{13}\\ &=\sum_{k=0}^\infty\sum_{n=0}^\infty\frac{2^{-n}}{(n+k+1)(k+1)}\tag{14}\\ &=\sum_{k=0}^\infty\frac1{(k+1)^2}+\sum_{k=0}^\infty\sum_{n=1}^\infty\frac{2^{-n}}{(n+k+1)(k+1)}\tag{15}\\ &=\frac{\pi^2}{6}+\sum_{n=1}^\infty\sum_{k=0}^\infty\frac{2^{-n}}{n}\left(\frac1{k+1}-\frac1{n+k+1}\right)\tag{16}\\ &=\frac{\pi^2}{6}+\sum_{n=1}^\infty\frac{H_n}{2^nn}\tag{17}\\ &=\frac{\pi^2}{4}\tag{18} \end{align} $$ Explanation:
$\ \:(9)$: change variables $n\mapsto n-m$
$(10)$: change order of summation
$(11)$: use the definition of $a_n$ from $(5)$
$(12)$: apply $(8)$
$(13)$: change order of summation
$(14)$: change variables $n\mapsto n+k$
$(15)$: pull out the $n=0$ terms
$(16)$: evaluate $\zeta(2)$ and use partial fractions
$(17)$: $H_n=\sum\limits_{k=0}^\infty\left(\frac1{k+1}-\frac1{n+k+1}\right)$
$(18)$: apply sum $(8)$ from this answer

share|improve this answer
1  
GREAT ANSWER! (+1) –  Chris's sis Dec 27 '13 at 8:45

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.